The current and future role of biomarkers in type 2 cytokine-mediated asthma management - Pavord, I; Afzalnia, S; Menzies-Gow, A; Heaney, L (Wiley, 2017)
Assessment and management of asthma is complicated by the heterogeneous pathophysiological mechanisms that underlie its clinical presentation, which are not necessarily reflected in standardized management paradigms and which necessitate an individualized approach to treatment. This is particularly important with the emerging availability of a variety of targeted forms of therapy that may only be appropriate for use in particular patient subgroups. The identification of biomarkers can potentially aid diagnosis and inform prognosis, help guide treatment decisions and allow clinicians to predict and monitor response to treatment. Biomarkers for asthma have been identified from a variety of sources, including airway, exhaled breath and blood. Biomarkers from exhaled breath include fractional exhaled nitric oxide, measurement of which can help identify patients most likely to benefit from inhaled corticosteroids and targeted anti-immunoglobulin E therapy. Biomarkers measured in blood are relatively non-invasive and technically more straightforward than those measured from exhaled breath or directly from the airway. The most well established of these are the blood eosinophil count and serum periostin, both of which have demonstrated utility in identifying patients most likely to benefit from targeted anti-interleukin and anti-immunoglobulin E therapies, and in monitoring subsequent treatment response. For example, serum periostin appears to be a biomarker for responsiveness to inhaled corticosteroid therapy and may help identify patients as suitable candidates for anti-IL-13 treatment. The use of biomarkers can therefore potentially help avoid unnecessary morbidity from high-dose corticosteroid therapy and allow the most appropriate and cost-effective use of targeted therapies. Ongoing clinical trials are helping to further elucidate the role of established biomarkers in routine clinical practice, and a range of other circulating novel potential biomarkers are currently being investigated in the research setting.